Fatty Acid Supplementation Affects Skin Wound Healing in a Rat Model - Hokynková, Alica; Nováková, Marie; Babula, Petr; Sedláčková, Miroslava; Paulová, Hana; Hlaváčová, Miroslava; Charwátová, Daniela; Stračina, Tibor (Nutrients, 2022)
Polyunsaturated fatty acids (PUFA) play an important role in reparative processes. The ratio of PUFAs n-3 to n-6 may affect wound healing. The study aimed to evaluate the effect of dietary supplementation with n-3 and n-6 PUFA in two proportions on skin wounds in laboratory rats. Adult male Wistar rats received 20% fat emulsion with a ratio of 1.4:1 (group A) or 4.3:1 (group B) for n-3:n-6 PUFAs at a daily dose of 1 mL/kg. The control group received water under the same conditions. The animals were supplemented a week before and a week after the skin excision performed on the back. The level of wound closure, various parameters of oxidative stress, and plasma fatty acids composition were evaluated. Wound tissue samples were examined by electron microscopy. The administration of fat emulsions led to significant changes in plasma polyunsaturated fatty acid composition. The increased production of reactive nitrogen species, as well as more numerous newly formed blood vessels and a greater amount of highly organized collagen fibrils in both groups A and B may indicate more intensive healing of the skin wound in rats supplemented with polyunsaturated fatty acids in high n-3:n-6 ratio.
Keywords: wound; Male; healing; Rats, Wistar; Fatty Acids, Omega-3; mastné kyseliny; polyunsaturated fatty acids; oxidative stress; omega-3 mastné kyseliny; mužské pohlaví; potkani Wistar; Fatty Acids; potravní doplňky; Dietary Supplements; krysa rodu Rattus; Animals; Fatty Acids, Unsaturated; Wound Healing; zvířata; Rats; nenasycené mastné kyseliny; 4-hydroxy-2-nonenal; hojení ran